Pengaruh Kecukupan Modal dan Efisiensi Operasional terhadap Kinerja Keuangan (Studi Kasus Bank Syariah Indonesia dan Bank Muamalat Periode 2019-2024): Pengaruh Kecukupan Modal dan Efisiensi Operasional terhadap Kinerja Keuangan - Layya Rahil; Kholifatul Rokhimah (FAKULTAS EKONOMI DAN BISNIS ISLAM, 2025)
In the economy, Islamic banks have a strategic role in collecting public funds and channeling them to productive sectors to encourage inclusive economic growth. To maintain the sustainability of its role, Islamic banks must manage financial performance optimally. Evaluation of financial performance can be done through key indicators such as Return on Assets (ROA), Return on Equity (ROE), BOPO, and Capital Adequacy Ratio (CAR). This study uses a comparative quantitative approach and applies multiple linear regression analysis to determine the relationship between capital adequacy and operational efficiency on financial performance. This study aims to analyze how CAR and BOPO affect Return on Assets (ROA) on Bank Muamalat and Bank Syariah Indonesia. This study uses a quantitative approach with secondary data obtained through annual financial reports, OJK publications, and academic references. The analysis technique used is multiple linear regression and descriptive analysis. The results of this study are expected to yield the finding that CAR and BOPO have a significant effect on ROA and ROE, with different strength and direction of influence on each bank. This anticipated finding will emphasize the importance of capital management and operational efficiency strategies that are adaptive to the characteristics of each institution.